RED FLAGS DALAM MENDETEKSI KECURANGAN: ANALISIS FAKTOR PEMICU FRAUD PADA LAPORAN KEUANGAN - Caesaria, Septia Mitha; Murti, Galuh Tresna; Mayasha, Efiearly (Jurnal Riset Akuntansi Politala, 2025)
This study aims to analyze the factors that have the potential to trigger fraud in financial statements and explore the role of red flags as early indicators of fraud detection. Through a literature review, this study identifies red flags and fraud risk factors that affect audit quality. This literature review covers various perspectives, including international regulations and guidelines such as ISA 240 and SAS 99, as well as empirical studies related to the role of red flags in detecting fraudulent financial reporting. Based on the analysis, red flags play a key role in mitigating the risk of financial information manipulation by detecting financial and operational anomalies that may indicate fraud. The results show that factors such as pressure, opportunity, and rationalization, described in the fraud triangle, contribute significantly to the occurrence of Fraudulent Financial Reporting. This study also underlines the importance of external auditors' knowledge of red flags, which can improve their effectiveness in detecting fraud regardless of demographic factors.